2010
DOI: 10.1007/s11430-010-4126-5
|View full text |Cite
|
Sign up to set email alerts
|

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago

Abstract: The expansion of inland Asia deserts has considerably influenced the environmental, social and economic activities in Asia. Aridification of inland Asia, especially timing of the initiation of Asian desertification, is a contentious topic in paleoclimatology. Late Cenozoic eolian loess-red clay sequences on the Chinese Loess Plateau, which possess abundant paleoclimatic and paleo-environmental information, can be regarded as an indicator of inland Asia desertification. Here we present a detailed magnetostratig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 279 publications
(185 citation statements)
references
References 45 publications
7
165
2
Order By: Relevance
“…This finding not only provides direct evidence of late Oligocene aridification in central Asia, but it also explains speculations of central Asian aridification based on eolian records, such as the appearance of dust deposition in the Junggar Basin [5] and the Loess Plateau [4] during the late Oligocene and the doubling of North Pacific eolian flux from the Eurasian continent during the same period [1,2].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This finding not only provides direct evidence of late Oligocene aridification in central Asia, but it also explains speculations of central Asian aridification based on eolian records, such as the appearance of dust deposition in the Junggar Basin [5] and the Loess Plateau [4] during the late Oligocene and the doubling of North Pacific eolian flux from the Eurasian continent during the same period [1,2].…”
Section: Discussionsupporting
confidence: 59%
“…Eolian records in deep-sea sediments [1,2] and dust deposits from the periphery of arid regions [3,4] have shown that central Asian aridity began to intensify from the late Oligocene to the early Miocene. Eolian deposits within central Asian arid regions [5] have implied that an arid pattern similar to that of today may have formed before the late Oligocene.…”
mentioning
confidence: 99%
“…Meanwhile, the eolian deposition also recorded the long-term process of aridification in inland Asia. The oldest eolian loess found in northern China appeared in the early Miocene (22)(23)(24)(25) [4,33,34], a critical period around which the environment transformed from a planetary circulation system into a monsoon-dominated pattern, as indicated by integrated studies of Asian paleoenvironmental records [35][36][37]. Both continental [38] and marine [39] eolian deposition records showed that aridification of inland Asia was significantly intensified during recent 3-4 Ma since the Pliocene.…”
Section: Geological Recordsmentioning
confidence: 99%
“…The reliability of the simulated response to the regional uplift also needs to be further improved, especially to consider how to reduce the dependence of the simulated results on the model and to lower the uncertainty on subcontinent scales. With regard to environmental change, eolian sediments in northern China [4,33,37], river and lake sediments [99], and reconstructions of environmental patterns from the geological-biological evidence [8,36,37] suggested that the formation of the East Asian monsoon was around 22-25 Ma. However, most of geological evidences about the South Asian monsoon were too short and the longest record was only about 12 Ma [29].…”
Section: Origin Of the South Asian And East Asian Monsoonsmentioning
confidence: 99%
“…Sun and Wang, 2005). The oldest loess deposits have now been dated to be 22 Ma (Guo et al, 2002) and possible even slightly older (Qiang et al, 2011). Recently it has been demonstrated, from the stratigraphy in the Xining Basin, that Asian palaeoenvironment is also governed by global climate changes.…”
Section: General Geologymentioning
confidence: 99%